Vibrotactile stimulus duration threshold for perception of pulse to vibration transition. - Remache-Vinueza, Byron; Trujillo-León, Andrés; Vidal-Verdú, Fernando (Springer Nature, 2025)
This study investigates the minimum stimulus duration required to perceive the transition from pulse to vibration sensations, a critical parameter for optimizing information transmission via haptic interfaces such as smartphones, tablets, smartwatches, game consoles, and sensory substitution systems. Efficient transmission relies on minimizing stimulus duration, enabling more information to be conveyed in less time. A preliminary experiment established intensity perception thresholds—the minimum vibration intensities detectable—at 40, 80, 150, 250, 300, and 590 Hz, frequencies primarily activating the Pacinian (Rapid Adapting II) psychophysical channel. Subsequently, 35 participants determined the minimum durations needed to perceive the transition from pulse to vibration sensations across this frequency range. Results revealed a consistent minimum duration of approximately 30 ms, contrasting with findings in audition, where shorter durations suffice at higher frequencies, but aligning with prior studies in tactile perception.
Keywords: Dispositivos hápticos; Vibraciones; Haptics; Vibration; Threshold; Pulse